Tradisi Mendem Ari-Ari, Makna Si Makna Simbolik Pada Tradisi Mendem Ari-Ari Dalam Masyarakat Suku Jawa Di Desa Rantau Indah Kabupaten Tanjung Jabung Timur - Febrianti, Vivi; Rukmana, Lisa (Krinok: Jurnal Pendidikan Sejarah dan Sejarah, 2024)
The research objectives include describing the symbolic meaning of the Mendem Ari-Ari tradition in the Javanese community in Rantau Indah Village, East Tanjung Jabung Regency, and the implementation of the Mendem Ari-Ari tradition in the Javanese community in Rantau Indah Village, East Tanjung Jabung Regency. This research uses historical research methods consisting of heuristics, source criticism, interpretation, and historiography. The results of this research are that the history of the Mendem Ari-Ari tradition is further strengthened by the Javanese people in Rantau Indah Village so that their Javaneseness does not disappear (a Javanese proverb says). Then it was socialized through more massive contact and communication from 2008 to 2018. The existence of the Mendem Ari-Ari tradition in Rantau Indah Village from 2008 to 2018 did not experience any change or fading of the tradition. Both in the way it is implemented and the knowledge of the people of Rantau Indah Village about the Mendem Ari-Ari tradition which is still carried out today. The Mendem Ari-Ari tradition is believed by the people of Rantau Indah Village to be an element of local tradition because it is a tradition that has been carried out and passed down from generation to generation.